Development Of Learning Devices Of Direct Teaching Model For Grade Vii Students On The Concept Of Quadrangles - Gappa, Usamah Maming (Professorline, 2024)
This study aims to produce a direct teaching model learning device for grade VII students on the concept of quadrilaterals. This study was conducted following the development stage of the 4-D learning model device from Thiagarajan . At the development stage , it was continued with the experimental stage which aimed to determine the effectiveness of the direct teaching model using the developed learning device, as well as to compare the learning outcomes of grade VII students on the concept of quadrilaterals taught with the direct teaching model compared to the learning outcomes of students taught with conventional learning. The learning devices developed were: (1) Learning Implementation Plan (RPP), (2) Student Worksheets (LKS), (3) Attitude and Performance Assessment Sheets, and (4) Learning Outcome Tests (THB). The results of the study showed that: (1) the direct teaching model learning device for grade VII students on the concept of quadrilaterals that was developed had met the criteria for a suitable learning device because it was declared valid by the validators, and at the trial stage, the teacher's ability to manage learning was categorized as good, student activities were categorized as effective, student responses were positive, and THB was valid, reliable and sensitive; (2) direct teaching model learning is effective for teaching the concept of quadrilaterals to grade VII students because 90% of students experienced learning completion, the teacher's ability to manage learning is categorized as good, student activities are categorized as effective, student responses are positive, and assessments of attitudes and performance are categorized as good; (3) the learning outcomes of grade VII students on the concept of quadrilaterals taught using direct teaching model learning are significantly better than the learning outcomes of students taught using conventional learning.